1965
DOI: 10.2307/3895489
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sub-Irrigated Meadow Vegetation to Application of Nitrogen and Phosphorus Fertilizer

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…A study in Montana showed that forbs did not respond to fertilizer treatments when seeded with more competitive grass species (Depuit and Coenenberg 1979). Russell et al (1965) found that N application decreased the percentage of legumes found in hay meadows in Nebraska. They also reported that P increased legume composition.…”
Section: Effects Of Fertilizermentioning
confidence: 94%
“…A study in Montana showed that forbs did not respond to fertilizer treatments when seeded with more competitive grass species (Depuit and Coenenberg 1979). Russell et al (1965) found that N application decreased the percentage of legumes found in hay meadows in Nebraska. They also reported that P increased legume composition.…”
Section: Effects Of Fertilizermentioning
confidence: 94%
“…The N X P interaction was quite similar in all years. Generally dry matter production exhibited a positive, linear response to increasing levels ofN with additional P while there was a quadratic response without additional P. Nitrogen and P together often produced higher yields than either applied separately (McMurphy et al, 197 5;Rehm, 1984;Rehm et al, 1972Rehm et al, , 1976Russell et al, 1965;Taliaferro et al, 1975). Results from our study indicated that P was apparently limiting at the higher N rates.…”
Section: Resultsmentioning
confidence: 49%
“…Early hay harvest and/or overgrazing shifted botanical composition (Weaver, 1954). Fertilization also altered species composition (Russell et al, 1965). Nitrogen fertilization promoted the invasion of cool-season grasses into warm-season grass stands, particularly ifN was applied in early spring or at rates high enough for residual N to accumulate (Rehm et al, 1976).…”
mentioning
confidence: 99%